2014
DOI: 10.1002/pip.2494
|View full text |Cite
|
Sign up to set email alerts
|

Composition and bandgap control in Cu(In,Ga)Se2 -based absorbers formed by reaction of metal precursors

Abstract: The control of composition and bandgap in chalcopyrite thin-film absorber layers formed by a metal precursor reaction is addressed. Two processes using reaction with either H 2 Se or H 2 S as the final step of a three-step reaction process were compared as follows: a three-step H 2 Se/Ar/H 2 S reaction and a three-step H 2 Se/Ar/H 2 Se reaction. In both processes, significant Ga homogenization was obtained during the second-step Ar anneal, but the third-step selenization resulted in Ga depletion near the Cu(In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Figure 7b shows the absolute values of the first derivative of EQE with respect to the wavelength, namely |dEQE/dλ|. The bandgap energies of the CIGS films were estimated from the local maxima of |dEQE/dλ| [30][31][32]. The local maxima of |dEQE/dλ| determined by using a quadratic fit were at the wavelengths of 1072 nm, 1073 nm, and 1082 nm for the CIGS films prepared by the single-stage, bi-layer, and three-stage processes, respectively, as illustrated in Figure 7a [33].…”
Section: Characteristics Of Cigs Solar Cells Prepared By Various Depomentioning
confidence: 99%
“…Figure 7b shows the absolute values of the first derivative of EQE with respect to the wavelength, namely |dEQE/dλ|. The bandgap energies of the CIGS films were estimated from the local maxima of |dEQE/dλ| [30][31][32]. The local maxima of |dEQE/dλ| determined by using a quadratic fit were at the wavelengths of 1072 nm, 1073 nm, and 1082 nm for the CIGS films prepared by the single-stage, bi-layer, and three-stage processes, respectively, as illustrated in Figure 7a [33].…”
Section: Characteristics Of Cigs Solar Cells Prepared By Various Depomentioning
confidence: 99%
“…Moreover, CuInSe 2 ’s formation temperature is relatively lower than that of CuInGaSe 2 31 . Since the bandgap increase is directly correlated with increases in Ga and S, the bottom layer should have a bandgap higher than the middle layer 2224,32 . On the other hand, the layer near surface also has a higher bandgap due to the high content of S, which was achieved by continuing sulfurization even after selenization 3336 .…”
Section: Resultsmentioning
confidence: 99%
“…This was mainly due to a significant increase in open‐circuit voltage ( V OC ) in the S‐rich film device. Several studies have shown that the sulfurization of CIGSe films substantially enhances the V OC and fill factor ( FF ) of solar cell devices compared to selenization‐only CIGSe cells . The increase in the band gap at the surface of the absorber layer (the absorber/buffer layer interface) was attributed to a reduction in recombination at the interface resulting in the increase in the V OC and the fill factor of sulfur‐incorporated CIGSSe solar cells .…”
Section: Resultsmentioning
confidence: 99%
“…its direct band gap and high absorption coefficient) . CIGSSe also has a band gap that is easily tunable by controlling its elemental ratios, which is helpful for both band‐gap grading of the absorber film and tandem solar cell design …”
Section: Introductionmentioning
confidence: 99%